ON ECONOMIC AND LEGAL ASPECTS OF PROPERTY (Globalization and Business, 2023)
The article deals with the issues of property as a fundamental economic category of the system of economic relations of societies. From the point of view of the methodology of analysis of property relations, economic and legal aspects are differentiated. In particular, in the first case, relations between subjects are implied in the process of production, distribution, exchange, and consumption of material goods (de facto), and in the second case, ownership (who owns what) (de jure). The economy (its functioning) is based on the actions of objective economic laws, while the law is based on subjective judgments and decisions. The privatization of property should not be an end in itself, but a way to effectively use the factors of production, which ultimately ensures economic growth. No form of ownership leads to an automatic increase in efficiency (the experience of post-Soviet reality has confirmed this). An analysis of the economics of crime and punishment is given.